Basamento paleoproterozoico del área de San Miguel, Sierras Septentrionales de la provincia de Buenos Aires: registro de una cuenca de retroarco en el margen sur del cratón del Río de La Plata - Lajoinie, María Florencia (2017)
New information obtained from the characterization of biotite gneises and migmatites from the San Miguel area allowed the interpretation of metamorphic processes that formed a portion of the Paleoproterozoic basement of the Tandilia Belt. Biotite gneiss shows a compositional Sj banding (N35°E/60°NW) and a mineral composition: microcline, (oligoclase-andesine), quartz and biotite. Migmatites oc- cur as differentiated bodies with stromatic structure with Sj orientation and quartz, oligoclase, microcline leucoso- mes. Also almandine gamet appears in voluminous leucosomes. Chemical analyses indícate that the gneiss derived from a sedimentary protolith (wacke) while the migmatites would have formed from partial melting of the gneiss through decomposition of biotite in presence of quartz and plagioclase. This fact must have generated the gametife- rous phase with potassic feldspar and a peraluminous granitic melt in imbalance: low ratio (La/Yb)N <55.85 and low Th and Zr contents. Migmatization must have started during the Transamazonian Cycle (~2200Ma) considering that most of the leucosomes are concordant with the banding gneiss orientation, formed during the mentioned Cycle. Thus, the pressure gradient favoured the migration and the intrusión of the melt (before to rebalance) into the gneiss and also in marbles generating metasomatism and skamification. This metamorphic evolution scheme matches with a tectonic context of back-arc basin associated with an oceanic-continental crust subduction that occu- rred during the Archaean-Paleoproterozoic period, and finished with the amalgamation of Tandilia Terrane to the Rio de la Plata Craton.